Multiplying insights from perturbation experiments: predicting new perturbation combinations - Joshua Welch (Molecular Systems Biology)
Graphical Abstract Experimentally exploring the effect of all perturbation combinations is not feasible. In their recent study, Theis and colleagues (Lotfollahi et al, 2023) present an approach that uses deep generative models to predict the effects of new perturbations from high‐throughput single perturbation experiments.